Perbandingan Konsep Ketepatan dalam Perbahasan Epistemologi Muslim Liberal dan Ahli Sunnah Wal Jamaah: Comparison of the Concept of Correspondence in the Epistemological Discourse in Liberal Muslims and Ahli Sunnah Wal Jamaah - Kamis, Maryam Habibah; Hamat, Mohd Fauzi; Wan Ramli, Wan Adli (Jurnal Usuluddin, 2024)
Correspondence is an important element of the Islamic epistemological debate. However, a survey of two schools of Islamic thought, namely liberal Muslims and Ahli Sunnah Wal Jamaah as presented by al-Baghdadi, found that each has a different conceptions of the concept of correspondence within their theory of knowledge. This article analyzes the comparison of the concept of correspondence in the epistemological debates of liberal Muslims and Ahli Sunnah Wal Jamaah. The results shows that liberal Muslims do not affirm the elemen of the meaning the correspondence of the meaning to the reality as it is since the theory is based on human contingency, sociological and psychological limitations and context in contrast to Ahli Sunnah Wal Jamaah who affirm the elemen of the meaning the correspondence of the meaning to the reality as it is. The whole formulation implies that correspondence must be affirm because correspondence is one of the elements of knowledge.